IMPLEMENTASI KEBIJAKAN DAN BUDAYA ORGANISASI TERHADAP KUALITAS PELAYANAN PUBLIK - ALOYSIUS RANGGA ADITYA NALENDRA; Sari Waty; Agus Suhaila (Widya Cipta - Jurnal Sekretari dan Manajemen, 2018)
This reseacrh analyzed about the implementation of policies and organizational culture on the quality of public services at Kecamatan Pamulang Tangerang Selatan. The writes used the method of descriptive quantitative method  with survey method as the tool. While for collection data, the writer  used cluster sampling technique with the number of respondents was 400. Moreover, for analyzing the data, the writer applied the multiple linear regression equation. The aim of this reseacrh was to find and to answer the hypothesis of the research. This reseach revealed the fact that there was a relationship between  the polices and culture organization  on the quality of public service.   Through this research, the writer finds the result that that there is significant influence between the implementation of policy and organizational culture on the quality of public services.Keywords: implementation of policies,organizational culture,the quality of public services